2021
DOI: 10.1177/02666669211052523
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of electronic commerce by individuals in Bangladesh

Abstract: With increased use of Internet and information technology platforms, e-commerce has experienced tremendous growth worldwide in the recent years. Although growing steadily in various digital services, Bangladesh has not been able to gain full advantages and benefits of e-commerce due to its poor adoption rate. This study aims at exploring the factors affecting e-commerce adoption in Bangladesh by applying an extended version of Unified Theory of Acceptance and Use of Technology (UTAUT) model which includes perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 112 publications
0
0
1
Order By: Relevance
“…It indicates that promoting conditions are insignificant and did not influence behavioural intention to use e-commerce services. The findings contrast Azam et al's (2021) findings, who investigated electronic commerce use in Bangladesh and concluded that facilitating conditions positively influence behavioural intention and actual use of electronic commerce.…”
Section: Figure 2 Results Of Structural Modelcontrasting
confidence: 99%
“…It indicates that promoting conditions are insignificant and did not influence behavioural intention to use e-commerce services. The findings contrast Azam et al's (2021) findings, who investigated electronic commerce use in Bangladesh and concluded that facilitating conditions positively influence behavioural intention and actual use of electronic commerce.…”
Section: Figure 2 Results Of Structural Modelcontrasting
confidence: 99%
“…, Model of PC Utilisation(Thompson et al, 1991), Motivational Model(Davis et al, 1992), Combined TAM and TPB(Taylor & Todd, 1995) Venkatesh et al (2003). combined eight conflicting hypotheses into a complete model that explained almost 70% of the variances in behavioural intention to accept and employ specific technologies(Azam et al, 2021). Compared to all other models for predicting technological acceptance and use, the UTAUT model performed the best in this study.…”
mentioning
confidence: 87%
“…The dominant framework employed in the literature is the Technology-Organization-Environment (TOE) framework proposed by Tornakzky and Fleischer (1990). However, this framework has several limitations, including generic constructs instead of contextual drivers Usman et al, 2019;Haryanti & Subriadi, 2020;Ugwuanyi et al, 2020;Azam et al, 2021). Therefore, scholars often adapt the constructs according to the specific study context, incorporating other theories to enhance rigor Sipahutar et al, 2020;Haryanti & Subriadi, 2020;Mullins & Cronan, 2021, Ayawei, 2022.…”
mentioning
confidence: 99%